2007
DOI: 10.1021/ef0700432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biodiesel Fuel on the Combustion and Emission Formation in a Direct Injection (DI) Diesel Engine

Abstract: This paper studies the influence of biodiesel fuel on the combustion and emission formation of two different direct-injected diesel engines, both employing different combustion processes. The research was focused on determining the influence of the specific combustion process on measurement results to ascertain if a generalization of the results is possible or whether they have to be interpreted as specific for specific engines. Standard D2 diesel fuel and commercial 100% biodiesel fuel were used. Tests were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…The raw OMWS oxygen content was reduced from 24.1 mass% to 5 mass% after pyrolysis at 450°C, which is equivalent to 79.2% deoxygenation of the OMWS by the red mud. The HHV of the red mud catalyzed pyrolysis oil ranged from 39.5-41.3 MJ/kg which is lower than that of D2-petrodiesel (42 MJ/kg) but higher than that of biodiesel (37.3 MJ/kg) [40]. A typical biodiesel fuel contains 10-12 mass% oxygen compared to the 5 mass% obtained for the OMWS red mud pyrolysis oil.…”
Section: Properties Of Liquid Pyrolysis Productsmentioning
confidence: 74%
“…The raw OMWS oxygen content was reduced from 24.1 mass% to 5 mass% after pyrolysis at 450°C, which is equivalent to 79.2% deoxygenation of the OMWS by the red mud. The HHV of the red mud catalyzed pyrolysis oil ranged from 39.5-41.3 MJ/kg which is lower than that of D2-petrodiesel (42 MJ/kg) but higher than that of biodiesel (37.3 MJ/kg) [40]. A typical biodiesel fuel contains 10-12 mass% oxygen compared to the 5 mass% obtained for the OMWS red mud pyrolysis oil.…”
Section: Properties Of Liquid Pyrolysis Productsmentioning
confidence: 74%
“…The sulphur and aromatics content of biodiesel fuels are negligible while their oxygen (O 2 ) concentration is substantially high (in the order of 10% on weight basis) [2]. These characteristics allow significant reductions of sulphur dioxide (SO 2 ), soot, carbon monoxide (CO) and unburned hydrocarbons (UHC) [3,4]. However, due to their influence on the ignition delay (ID), the production of nitrogen oxides (NO x ) during combustion is usually increased [5].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers Hribernik and Kegl [36] have reported that the combustion and emission formation, particularly the increase of NO x emissions by application of biodiesel varies significantly with different combustion systems and different combustible mixture formation strategies. Pasupathy Venkateswaran and Nagarajan [37] have carried out simulation studies to investigate the effect of piston bowl geometry on both engine performance and combustion efficiency in a direct injection, turbocharged diesel engine for heavy-duty applications using STAR-CD.…”
Section: Introductionmentioning
confidence: 99%